Strengthening the social resilience of people living at the intersection of precariousness and migration during pandemics: action recommendations developed in Munich, Germany - Öcek, Zeliha Asli; Geise, Mandy; Volkmann, Anna-Maria; Basili, Acelya; Klünder, Vera; Coenen, Michaela (Frontiers in Public Health, 2023)
Introduction An EU-funded project in five countries examined vulnerability mechanisms during the COVID-19 pandemic. The research team in Germany concentrated on people living at the intersection of migration and precariousness. The study aimed first to provide an understanding of how migrants living in precarious conditions in Munich had been affected by the pandemic, both from their own and from experts’ perspectives. The second aim was to develop action recommendations to reduce structural vulnerabilities and increase resilience with a view towards improved pandemic preparedness. Methods The study followed a two-phase process. The first was a qualitative study based on interviews with 25 migrants and 13 experts. In the second, researchers developed action recommendations based on the vulnerability/ resilience factors that had been generated in the first phase. Three consecutive meetings with stakeholders (expert panel, focus group discussion with two migrant organization, meeting with the Munich Migration Council) were then held to further strengthen the draft recommendations. Results Content analysis revealed twelve vulnerability and eight resilience factors in three domains (COVID-19 prevention; human rights, living and housing environment; social support). Migrants had limited access to COVID-19 prevention measures; living conditions made outbreaks inevitable; uncertainty about legal status, employment, and housing, as well as stigma and discrimination, exacerbated their precariousness; social support had decreased; and resilience mechanisms had failed. The initial draft of recommendations contained 24 proposed actions. The meetings added recommendations such as enhancing psychosocial support, preventing ghettoization, improving social housing, preventing the interruption of language education in times of crisis, severe penalties for media stigmatisation and proactive truth-telling. The final list included 30 actions. Conclusion In Munich, the COVID-19 pandemic exacerbated vulnerability mechanisms commonly associated with being a migrant. The recommendations developed here speak to those vulnerabilities but need to be refined further to be more actionable and comprehensive. Nonetheless, the recommendations and the processes that led to them highlight the importance of migrant-inclusive approaches and empowerment in increasing migrants’ resilience to future crises.